THE IMPACT OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT LPP RRI JEMBER - Dinanti, Hilda Setia; Winahyu, Pawestri; Reskiputri, Tatit Diansari (Universitas Muhammadiyah Tangerang, 2024)
This study was conducted at LPP RRI Jember which aims to determine the effect of transformational leadership style, organizational culture and work motivation on employee performance at LPP RRI Jember. The analysis was conducted on the performance of 83 employees of LPP RRI Jember using saturated sampling techniques and data collection techniques were carried out by means of observation and distributing questionnaires to all employees of LPP RRI Jember about various information / data needed using a Likert scale while data analysis used multiple regression methods with the help of the SPSS program. Company leaders should be able to provide motivation to subordinates both in moral and material form to improve employee performance and foster an attitude of loyalty to the company. Leaders are also required to pay more attention to the policies taken in leading the company, and determine a good leadership strategy or style in order to create a conducive work atmosphere between superiors and subordinates.